The Influence of Electronic Word of Mouth and Financial Literacy on Digital Banking Product Purchase Decisions - Amilia Paramita Sari; Anisah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
This research aims to investigate the influence of E-WOM (electronic word of mouth) and financial literacy on the purchasing decisions of digital banking products with a case study on state-owned banks in Indonesia during the period 2022-2024. As many as 100 respondents who are users of digital banking products from state-owned banks (BUMN) were sampled in this study. The method used is multiple regression analysis to test the relationship between independent variables (E-WOM and financial literacy) and the dependent variable (purchase decision). The research results show that both variables, namely E-WOM and financial literacy, have a significant positive influence on the purchase decisions of digital banking products. Moreover, E-WOM and financial literacy mutually reinforce each other in influencing consumer purchase decisions. This research provides practical implications for state-owned banks to leverage positive consumer reviews and enhance customers' financial literacy as a strategy to increase the adoption of digital banking products. These findings also contribute to the understanding of the factors influencing purchasing decisions in the context of digital banking in Indonesia.